2021
DOI: 10.1007/s11136-021-02938-7
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian population norms for the EQ-5D-5L: results from a general population survey

Abstract: Purpose To provide the first Norwegian EQ-5D-5L and EQ VAS population norms for the adult general population. Methods Postal survey of a random sample of 12,790 Norwegians identified through the National Registry of the Norwegian Tax Administration. Norms, weighted for Norwegian general population characteristics, are shown for the five EQ-5D-5L dimensions, EQ-5D index, and EQ VAS scores for seven age categories, females, males, and education level. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 36 publications
6
43
5
1
Order By: Relevance
“…The patients reported moderate levels of depression and/or anxiety, which would not usually entail difficulties with mobility or washing and dressing. Overall, patients in the study reported more problems across all dimensions compared to the respondents in the study that collected the Norwegian EQ-5D norm data (Garratt et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The patients reported moderate levels of depression and/or anxiety, which would not usually entail difficulties with mobility or washing and dressing. Overall, patients in the study reported more problems across all dimensions compared to the respondents in the study that collected the Norwegian EQ-5D norm data (Garratt et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…A minority of patients reported problems on the Mobility and Self-care; 24.3 and 15.2%, respectively, whilst a large majority of patients in the sample reported some level of problems on Usual activities and Pain/ discomfort (78.3 and 76.2%, respectively). Figure 1 shows a comparison between the proportion of patients in the present study and the proportion of participants in the study obtaining data for the general population norms (Garratt et al, 2021) reporting "No problems" on the sub-scales. The patient cohort reported more problems on all dimensions compared to the norm population.…”
Section: Known-groups Validitymentioning
confidence: 98%
See 3 more Smart Citations